Human capital and Black-white earnings gaps, 1996-2017 - Owen Thompson (W.E. Upjohn Institute for Employment Research, 2021)
This paper estimates the contribution of human capital to the Black-white earnings gap in three separate samples of men spanning from 1966 through 2017, using both educational attainment and performance on standardized tests to measure human capital. There are three main findings. First, the magnitude of reductions in the Black-white earnings gap that occur after controlling for human capital has become much larger over time, suggesting a growing contribution of human capital to Black-white earnings disparities. Second, these increases are almost entirely due to growth in the returns to human capital, which magnify the impact of any racial differences in human capital levels, rather than to increasing racial gaps in the human capital traits themselves. Finally, growth in the explanatory power of human capital has been primarily due to increases in the association between human capital and the likelihood of nonwork, with no clear increases in the extent to which human capital explains Black-white wage differences. These findings highlight how apparently race-neutral structural developments in the U.S. labor market, such as increasing skill prices and falling labor force participation rates among less-skilled men, have had large impacts on racial inequity.
Keywords: J15; J24; J31; J71; 330; human capital; earnings gap; racial gap; black-white; NLS; decomposition